Team Game Tournament with Crossword Puzzle Media as a Pedagogical Tool for Balaghah Learning in Higher Education - Hasibuan, Renni; Hasanah, Mamluatul; Faisol; Siti Nur'ain Binti Ahmad Radzuanuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Using diverse methods enhances student interest and creativity, making learning more engaging. This research aimed to explore how the Team Game Tournament (TGT) method using crossword puzzles is applied in teaching Balaghah, focusing on three key activities: the preliminary activity, the main activity, and the final activity, and how students responded to the application of this method. This research used a descriptive qualitative method, with data collection techniques including observation and questionnaires. The results of this research are as follows: 1) The preliminary activity included greetings, opening the lesson with a prayer, and reminding students of previously learned concepts or knowledge. 2) In the main activity, five organized stages were applied: in-class presentation, group learning, the game, the tournament, and finally, the group reward. 3) In the final activity, the session's conclusions were presented, along with the ideas gained during the learning process, and the lesson was concluded with a prayer. 4) The students' response to the application of this method received a score of 82.2%, rated as